2011
DOI: 10.1021/jp2087412
|View full text |Cite
|
Sign up to set email alerts
|

Increased Stability Toward Oxygen Reduction Products for Lithium-Air Batteries with Oligoether-Functionalized Silane Electrolytes

Abstract: The successful development of Li-air batteries would significantly increase the possibility of extending the range of electric vehicles. There is much evidence that typical organic carbonate based electrolytes used in lithium ion batteries form lithium carbonates from reaction with oxygen reduction products during discharge in lithium-air cells so more stable electrolytes need to be found. This combined experimental and computational study of an electrolyte based on a tri(ethylene glycol)-substituted trimethyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
174
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 167 publications
(189 citation statements)
references
References 37 publications
11
174
1
3
Order By: Relevance
“…The slightly higher yields indicate that the relatively high surface area of the Li 2 O 2 film that grows on the electrode in the absence of DBBQ leads to more decomposition of the electrolyte solution than is the case for the large particles in solution. It has also been suggested that LiO 2 is responsible for solvent decomposition on discharge 26,41,42 and, as discussed below, our analysis points to a mechanism that avoids this reactive intermediate. Attempts to charge the cells after discharge proved fruitless (see Supplementary Fig.…”
Section: Cyclic Voltammetry Studies With Dbbqsupporting
confidence: 68%
“…The slightly higher yields indicate that the relatively high surface area of the Li 2 O 2 film that grows on the electrode in the absence of DBBQ leads to more decomposition of the electrolyte solution than is the case for the large particles in solution. It has also been suggested that LiO 2 is responsible for solvent decomposition on discharge 26,41,42 and, as discussed below, our analysis points to a mechanism that avoids this reactive intermediate. Attempts to charge the cells after discharge proved fruitless (see Supplementary Fig.…”
Section: Cyclic Voltammetry Studies With Dbbqsupporting
confidence: 68%
“…The cathode may contain a catalyst in some form to promote the discharge reaction. It has been found that a variety of factors dictate the nature of electrochemical reactions in Li-air cells including the nature of the catalyst, the catalyst distribution on the porous cathode, the pore volume of the cathode and the type of organic electrolyte used [3][4][5][6][7][8][9][10] .…”
mentioning
confidence: 99%
“…Some of the early work on Li-O 2 batteries was based on carbonate electrolytes including catalysts such as aMnO 2 , Co 3 O 4 , Mn 3 O 4 and PtAu [11][12][13][14][15] . However, carbonate electrolytes were found to decompose in Li-O 2 batteries 1,16,17 and consequently researchers turned to ether-based electrolytes, which have greater stability 8,11,18 . In a dimethoxyethane-based electrolyte, McCloskey et al 19 investigated the electrocatalytic role of Au, Pt and MnO 2 nanoparticles and found that none of these nanoparticles performs better than just a carbon surface.…”
mentioning
confidence: 99%
“…These studies included different carbons [6][7][8] and polycrystalline metal surfaces such as nanoporous gold 9,10 , all of which have a variety of active sites. Other studies have reported supported nanoparticles as electrocatalysts in Li-O 2 cells [11][12][13][14][15] . In addition, during the deposition process of nanoparticles it is possible that small clusters may also be present that are acting as electrocatalysts as has been found in surface reactions involving gold clusters 16 .…”
mentioning
confidence: 99%